Emerging infrastructure policy issues in developing countries : a survey of the recent economic literature - Estache, Antonio 1957- (Policy research working paper, 2004)
"Estache reviews the recent economic research on emerging issues for infrastructure policies affecting poor people in developing countries. His main purpose is to identify some of the challenges the international community, and donors in particular, are likely to have to address over the next few years. He addresses six main issues: (1) the necessity of infrastructure in achieving the Millennium Development Goals; (2) the various dimensions of financing challenges for infrastructure; (3) the debate on the relative importance of urban and rural infrastructure needs; (4) the debate on the effectiveness of infrastructure decentralization; (5) what works and what does not when trying to target the needs of the poor, with an emphasis on affordability and regulation challenges; and (6) the importance of governance and corruption in the sector. The author concludes by showing how the challenges identified define a relatively well integrated agenda for both researchers and the international infrastructure community. This paper,a product of the Office of the Vice President, Infrastructure Network,is part of a larger effort in the network to stimulate more analytical assessments of emerging issues in the sector"--World Bank web site